Database DNDC paper - Latin America Greenhouse Gas Mitigation Network (International Center for Tropical Agriculture, 2017)
This database have the modelled data from simulation of urine and manure patches in a livestock system in Colombia and measured data in order to validate the modelled values. The parameter simulated was N2O flux.